Information sharing for situational understanding and command coordination in emergency management and disaster response - Desourdis, R. I.; Contestabile, J. M. (2011 IEEE International Conference on Technologies for Homeland Security, 2011)
This paper explores why information sharing is important to successfully dealing with large-scale events and how a lack of public safety communications systems interoperability is a major impediment. It describes how "holistic interoperability," which addresses matters of trust and understanding that lead to predictable collaboration, is needed and how the lessons from the lack of information sharing during Pearl Harbor remains instructive today. It goes on to describe how a conceptual technical framework of information layers (i.e., the data, integration and presentation layers) is useful to developing solutions to this lack of interoperability. It also postulates how emerging technologies will move us from today's flawed "publish-and-subscribe" environment, which suffers from many of the "Pearl Harbor failures," to an automated preplanned "sense-and - respond" model. Work reported herein was derived from an Urban Area Security Grant as part of interoperable communications programs for the National Capital Region (NCR).